AN ANALYSIS OF SELECTED ELEVENTH GRADE ENGLISH TEXTBOOKS - Akbar, Rizky (2016)
Textbooks play a pivotal role in language classrooms in all types of educational institutions. However, textbook selection and evaluation is often given little time or attention despite its central role in most language courses. This study aimed at determining to what extent are two selected eleventh grade English textbooks appropriate in terms of content based on BSNP framework for textbook evaluation. Using descriptive qualitative method, this study attempted to find out the appropriateness of the content of the textbooks. A checklist adapted from BSNP (2014) framework for textbook evaluation was made, focused on the areas of relevance of materials with competency standards and basic competencies, materials accuracy, and supporting learning materials. The findings show that both textbooks were appropriate in terms of content based on BSNP framework for textbook evaluation.;--- Buku teks memegang peranan penting dalam kelas bahasa di berbagai institusi pendidikan. Akan tetapi, pemilihan serta evaluasi buku teks seringkali hanya diberikan sedikit waktu dan perhatian meski perannya yang sangat penting dalam banyak pelajaran bahasa. Penelitian ini bertujuan untuk menentukan sejauh mana materi yang terdapat dalam dua buku teks Bahasa Inggris yang telah dipilih sesuai dengan kerangka evaluasi buku teks BSNP. Dengan menggunakan metode deskriptif kualitatif, penelitian ini berusaha untuk mencari tahu kelayakan isi buku teks. Sebuah ceklis yang diadaptasi dari kerangka evaluasi buku teks BSNP (2014) yang berfokus pada area kesesuaian uraian materi dengan Kompetensi Inti dan Kompetensi Dasar, keakuratan materi, dan materi pendukung pembelajaran. Hasil penelitian menunjukkan bahwa kedua buku teks memiliki isi yang layak berdasarkan kerangka evaluasi buku teks BSNP.